As Long as They Dont Bury Me Here : Social Relations of Poverty in a Namibian Shantytown - Tvedten, Inge (Book collections on Project MUSE., 2011)
An increasing number of poor Southern Africans live in poverty-stricken urban slums or shantytowns. Focusing on four shantytowns in the northern Namibian town of Oshakati, this book analyses the coping strategies of the poorest sections of such populations. The study is based on fieldwork conducted intermittently during a period of 10 years. It combines theories of political, economic and cultural structuration, and of the material and cultural basis for social relations of inclusion and exclusion as practise. The poorest shanty dwellers are marginalised or excluded from vital urban and rural relationships and forced into social relations of poverty amongst themselves. Having experienced long-term processes of impoverishment, the very poorest and most destitute in the shantytowns tend to give up improving their lives and act in ways that further undermine their position.